Design and Development of a Lower Limb Rehabilitation Device for Spinal Cord Injury Patients - Trusler, Matthew (Department of Human Biology, 2022)
Introduction: Spinal cord injuries (SCI) are seen commonly in Southern Africa and can completely change the course of the affected's life. Lower limb disability is a common complication from this injury, but a patient can be rehabilitated in some cases. Research and clinical observations suggest that early mobilisation and rehabilitation leads to shorter hospital stays and better clinical outcomes. Relieving the time dedication placed onto the rehabilitation team could mean that patients receive a higher standard of care. Methods: A cyclic movement device has been designed to mimic the gait cycle that a patient is attempting to recover. The device was intended towards providing a ground reaction force simulation at the correct points of the gait cycle. The device was tested in-silico with validated skeletal models to determine joint torques and angles. In-silico testing was also utilised to determine the loads placed onto the patient by the device through its use. The force data could then be used to predict possible ground reaction forces. Results: The device allows for a gait similar trace path of the ankle, comparable to that found in the literature. The ankle has a range of motion of 3 1° as the device completes a full cycle in which the crank rotates 360 °. The hip has a range of motion of 28° and the knee 35° in this same movement. The shape of the displacements of the joints of the lower limb is comparable to that seen in researched gait patterns. However, the timing of the knee and hip joints' movements are not synchronous with that of the gait patterns. The device is validated to be sufficiently stable to use, and the motor and power components can provide the 7259N.mm of torque needed to move the model. Conclusion: The results suggest that the device has potentia l as an adjunct to rehabilitation schemes. In-silico testing showed that the device is able to simulate some of the kinetic and kinematic parameters seen in normal gait. Further work is needed to prototype the device to physically and clinically validate the device.